The effect of combinations of iron-bearing minerals and quartz on coke reactivity. (14th September 2018) - Longbottom, Raymond J.; Monaghan, Brian J.; Chowdhury, Azrin A.; Mahoney, Merrick R.; Reid, Mark H.; Zhang, Guangqing; Hockings, Kim
ABSTRACT: The effect of combinations of iron-bearing minerals and quartz on the reactivity of coke analogues with CO2 was examined in a TGA. Troilite–quartz, pyrite–quartz and magnetite–troilite binary combinations and the troilite–magnetite–quartz ternary combination were examined. For the troilite–quartz and pyrite–quartz binary combinations the reactivity in general decreased non linearly with increasing Si:Fe ratio. The magnetite–troilite combination had a non-linear effect on the reactivity in that mixes of these two minerals show a higher reactivity than would be expected from a simple proportional mixing approach. Some evidence of sulphur transfer from the troilite to the magnetite was observed. The reactivity of the ternary magnetite–troilite–quartz combination can largely be understood from the trends in the axes. These were largely followed across all compositions, allowing better understanding and prediction of the effect of these minerals on the reactivity of industrial cokes.